Practical performance analysis of an industrial-scale ultrafiltration membrane water treatment plant - Chew, C.M.; Aroua, M.K.; Hussain, Mohd Azlan; Wan Ismail, W.M.Z. (Elsevier, 2015)
Common design and operational issues to evaluate the performance of an ultrafiltration (UF) membrane water treatment plant are highlighted with a case study on an industrial-scale drinking water treatment plant located in Malaysia. This treatment plant has been in operation since February 2013 using dead-end polyethersulfone UF membrane filtration system to produce up to 14 million litres a day of drinking water to a small township. Literature solutions are compared with the practised solutions and elucidated with the case study. Gaps between literature solutions which are mainly based on lab-scale research and industry practices are identified. Reducing this gap will have vast implication to improve the design and operation of industrial-scale UF treatment system. (C) 2014 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.